Preparation method of high-temperature-resistant mold with micro-nano structure array and metal mold
By processing the micro-nano structure on the master mold and plating an anti-adhesive film on the metal glass template, the mold adhesion problem is solved, the anti-adhesive ability and bond reliability of the mold are improved, the service life of the mold is extended and the quality of the mold is ensured.
Patent Information
- Application Number
- CN202510287422.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-10
- Publication Date
- 2025-06-03
AI Technical Summary
Existing molds are prone to sticking when glass is hot pressed, resulting in difficulty in precision preparation of glass elements, and insufficient anti-adhesion and bonding stability of existing coating materials.
The high-temperature resistant mold preparation method with a micro-nano structure array is adopted. By processing the micro-nano structure on the master mold, the micro-nano structure is copied using a template made of metal glass, and an anti-adhesive film is plated on the template to form a metal mold.
It improves the anti-bonding ability of the metal mold and the bonding reliability of the coating, enhances the stability and service life of the mold in high temperature environments, and ensures the quality of the molded optical components.
Smart Images

Figure CN120080123A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of amorphous alloy molds, and particularly relates to a preparation method of a high-temperature resistant mold with a micro-nano structure array and a metal mold. Background Art
[0002] At present, glass microlens arrays (MLAs) have unique advantages in optical sensing, beam conversion, and imaging. Using a metal mold for glass compression molding (PCM) is considered the most attractive method for mass-producing glass MLA components.
[0003] However, when the existing mold is used for hot pressing of glass, the surface of the mold usually adheres to the formed glass material, hindering the precise preparation of glass components. Usually, a thin film needs to be coated on the mold surface to reduce the adhesion force. However, existing coating materials such as metal alloy coatings, ceramic coatings, and diamond-like carbon films (DLC) have problems of low anti-adhesion and poor bonding stability. Summary of the Invention
[0004] The purpose of the embodiments of the present application is to provide a preparation method of a high-temperature resistant mold with a micro-nano structure array, aiming to solve the problems of how to improve the anti-bonding of the metal mold and the bonding reliability of the coating.
[0005] To achieve the above purpose, the technical solution adopted in the present application is as follows:
[0006] In the first aspect, a preparation method of a high-temperature resistant mold with a micro-nano structure array is provided, which includes the following steps:
[0007] Mold making: preparing a master mold, on which a micro-nano structure is processed;
[0008] Cutting: preparing raw materials, the material of the raw materials is metallic glass, and a template with a predetermined shape is cut out on the raw materials;
[0009] Copying: heating to soften the template, and enabling the template to copy the micro-nano structure;
[0010] Coating: coating an anti-bonding film on the template, the material of the anti-bonding film is metallic glass, and the anti-bonding film covers the micro-nano structure to process the template into a metal mold.
[0011] In some embodiments, the material of the template is Zr-based amorphous alloy, Pd-based amorphous alloy, Pt-based amorphous alloy, or La-based amorphous alloy; the material of the anti-bonding film is Ir-based amorphous alloy.
[0012] In some embodiments, in the coating step, an Ir-based amorphous alloy is used as a target, and the template is coated by pulsed laser deposition technology to deposit the anti-adhesion film on the template.
[0013] In some embodiments, the pulsed laser deposition technology is implemented using a pulsed laser emitter with a frequency of 2 Hz and a single pulse energy of 50 mJ.
[0014] In some embodiments, the template has a first coefficient of thermal expansion, and the anti-adhesion film has a second coefficient of thermal expansion. The ranges of both the first coefficient of thermal expansion and the second coefficient of thermal expansion are greater than zero and less than 10 ppm / K.
[0015] In some embodiments, the template is circular, and the diameter range of the template is 2 - 15 mm, and the thickness range of the template is 1 - 5 mm.
[0016] In some embodiments, the replication step includes the following steps:
[0017] S31: Polish the template;
[0018] S32: Stack the template and the master mold and place them together in a heating chamber, and evacuate the heating chamber;
[0019] S33: Apply a first predetermined pressure to the template to press the master mold and the template tightly;
[0020] S34: Heat the template to a first predetermined temperature, and increase the first predetermined pressure to a second predetermined pressure, where the second predetermined pressure is greater than the first predetermined pressure, so that the template replicates the micro-nano structure;
[0021] S35: Then heat the template to a second predetermined temperature, where the second predetermined temperature is greater than the first predetermined temperature, to crystallize the template with the replicated micro-nano structure.
[0022] In some embodiments, the S34 step includes:
[0023] S331: At the second predetermined temperature, maintain the second predetermined pressure and keep the template and the master mold at a constant temperature for a predetermined time;
[0024] S332: Cool the template to a third predetermined temperature and unload the second predetermined pressure, where the third predetermined temperature is less than the first predetermined temperature;
[0025] S333: Cool the template to room temperature.
[0026] In some embodiments, the first predetermined temperature is 470 degrees Celsius, the second predetermined temperature is 550 degrees Celsius, and the third predetermined temperature is 450 degrees Celsius.
[0027] In a second aspect, a metal mold is provided, which is prepared by the method for preparing a high-temperature resistant mold with a micro-nano structure array as described above.
[0028] The beneficial effects of the present application are as follows: By processing a micro-nano structure on the master mold, thermoplastically replicating the micro-nano structure using a template made of metallic glass, and then depositing an anti-adhesion film on the micro-nano structure of the template, a metal mold is prepared by a non-mechanical method. Since the materials of both the template and the anti-adhesion film are metallic glass, a stable connection is easily formed, so that the anti-adhesion layer and the template have a relatively high bonding strength, improving the stability and reliability of the metal mold during the optical glass forming process. Moreover, the metallic glass material of the anti-adhesion film can reduce the adhesion between it and the optical glass, thereby extending the service life of the metal mold and ensuring the quality of the formed optical components. Description of the Drawings
[0029] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or exemplary technical descriptions will be briefly introduced below. Obviously, the drawings in the following description are only some embodiments of the present application. For those of ordinary skill in the art, other drawings can be obtained based on these drawings without creative efforts.
[0030] Figure 1 is a flowchart of the method for preparing a high-temperature resistant mold with a micro-nano structure array provided by an embodiment of the present application;
[0031] Figure 2 is a schematic diagram of the replication step of the method for preparing a high-temperature resistant mold with a micro-nano structure array provided by another embodiment of the present application;
[0032] Figure 3 is a schematic diagram of the film coating step of the method for preparing a high-temperature resistant mold with a micro-nano structure array provided by still another embodiment of the present application;
[0033] Figure 4 is a schematic diagram of the hot pressing method provided by yet another embodiment of the present application;
[0034] Figure 5 is a heating curve diagram of the metal mold and the optical glass provided by still another embodiment of the present application.
[0035] Among them, the reference numerals in the drawings are as follows:
[0036] 10. Master mold; 20. Template; 30. Metal mold; 40. Optical glass; 50. Pulsed laser emitter; 101. Micro-nano structure; Detailed implementation manners
[0037] In order to make the objectives, technical solutions and advantages of the present application clearer, the present application will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present application.
[0038] It should be noted that when a component is referred to as "fixed to" or "disposed on" another component, it can be directly on the other component or indirectly on the other component. When a component is referred to as "connected to" another component, it can be directly or indirectly connected to the other component. The orientation or positional relationship indicated by terms such as "upper", "lower", "left", "right", etc. is based on the orientation or positional relationship shown in the accompanying drawings, and is only for the convenience of description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation of the present application. For those of ordinary skill in the art, the specific meanings of the above terms can be understood according to specific circumstances. Terms "first" and "second" are only used for the purpose of convenient description and cannot be understood as indicating or implying relative importance or implicitly indicating the quantity of technical features. The meaning of "a plurality" is two or more, unless otherwise specifically defined.
[0039] Please refer to Figures 1 to 3 , the embodiment of the present application provides a preparation method of a high-temperature resistant mold with a micro-nano structure 101 array and a metal mold 30 prepared by this method. The metal mold 30 can hot-press the optical glass 40 into an optical element, and the material of the optical glass 40 can be D-K9 or BK7.
[0040] Please refer to Figures 2 to 4 , the preparation method of a high-temperature resistant mold with a micro-nano structure 101 array, which includes the following steps:
[0041] S1: Mold making, preparing the master mold 10, and processing the micro-nano structure 101 on the master mold 10; in this embodiment, the master mold 10 is a silicon template, and the micro-nano structure 101 can be processed on the silicon template through etching technology or single-point diamond turning technology to process the silicon template into the template 20.
[0042] The micro-nano structure 101 is a structure with a size in the nanometer scale and / or micrometer scale. The micro-nano structure 101 can be a micro-bump or a micro-indentation. For example, the micro-nano structure can be a lens array, a grating array, or a cylinder array, etc. Among them, in the lens array, the diameter range of a single lens can be 10 nm to 5 mm; in the grating array, the range of a single groove width structure can be 10 nm to 5 mm; in the cylinder array, the diameter range of a single cylinder can be 10 nm to 5 mm. In this embodiment, the micro-nano structure is a lens array, and the diameter of a single lens can be 10 nm, 20 nm, 100 nm, 200 nm, 80 μm, 1 mm, 2 mm, 3.3 mm, or 5 mm. In other embodiments, the micro-nano structure can be selected according to the actual situation, and no limitation is made here.
[0043] S2: Cutting, preparing the raw material. The material of the raw material is metallic glass, and a template 20 with a predetermined shape is cut out on the raw material. In this embodiment, the shape of the template 20 is circular, and the diameter range of the template 20 can be 2 to 15 mm, such as 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 8.5 mm, 9 mm, 9.3 mm, 9.5 mm, 9.8 mm, 10.5 mm, 11.6 mm, 12 mm, 13 mm, 14 mm, 14.1 mm, 15 mm; the thickness range of the template 20 can be 1 to 5 mm, such as 1 mm, 1.5 mm, 2 mm, 2.3 mm, 2.4 mm, 2.5 mm, 2.6 mm, 2.8 mm, 2.9 mm, 3 mm, 3.5 mm, 3.8 mm, 4 mm, 4.5 mm, 4.9 mm, 5 mm. In this embodiment, the diameter of the template 20 is 10 mm, and the thickness of the template 20 is 3 mm. In other embodiments, it can be selected according to the actual situation, and no limitation is made here. Metallic glass is also called amorphous alloy, which is a kind of metallic material with a unique atomic structure, and its characteristic is that the atomic arrangement shows long-range disorder and short-range order.
[0044] S3: Copying, please refer to Figure 2 , heating to soften the template 20 and enabling the template 20 to copy the micro-nano structure 101. It can be understood that the temperature of the template 20 is heated to its glass transition point temperature through a heating structure, so that the template 20 is in a softened state, and then pressure is applied on the template 20 to enable the template 20 to copy the micro-nano structure 101 on the master mold 10. The micro-nano structure 101 on the template 20 and the micro-nano structure 101 on the template 20 are in a mirror image relationship.
[0045] S4: Coating, please refer to Figure 3, an anti - adhesion film is deposited on the template 20. The material of the anti - adhesion film is metallic glass, and the anti - adhesion film covers the micro - nano structure 101 to process the template 20 into a metal mold 30. It can be understood that multiple micro - nano structures 101 are arranged in an array on the master mold 10, so that multiple micro - nano structures 101 are also arranged in an array on the metal mold 30.
[0046] Please refer to Figures 2 to 4 , in this application, by processing the micro - nano structure 101 on the master mold 10, using the thermoplasticity of the template 20 made of metallic glass to replicate the micro - nano structure 101, and then depositing an anti - adhesion film on the micro - nano structure 101 of the template 20, a metal mold 30 is prepared by a non - mechanical method. Since the material of the template 20 and the material of the anti - adhesion film have the same elements, there is an element diffusion during the combination process. Some elements of the template 20 diffuse into the anti - adhesion film, and some elements in the anti - adhesion film also diffuse into the template 20, strengthening the combination between the template 20 and the anti - adhesion film, making it easy to form a stable connection between the template 20 and the anti - adhesion film. Thus, there is a relatively high bonding force between the anti - adhesion layer and the template 20, improving the stability and reliability of the metal mold 30 during the forming process of the optical glass 40. Moreover, the metallic glass material of the anti - adhesion film can reduce the adhesion between it and the optical glass 40, thereby extending the service life of the metal mold 30 and ensuring the quality of the formed optical elements.
[0047] The preparation method of the high - temperature - resistant mold with an array of micro - nano structures 101 provided by this application prepares the metal mold 30 by a non - mechanical preparation method, avoiding the limitations of traditional mechanical processing (such as milling or laser engraving), being able to efficiently replicate complex micro - nano structures 101 at the micron and / or nanometer levels, and improving the dimensional accuracy and surface quality of the metal mold 30.
[0048] Optionally, in the embodiments of this application, the structure of the micro - nano structure 101 on the metal mold 30 is a lens array, and the diameter of a single lens can be 75μm or 400nm.
[0049] In some embodiments, the material of the template is Zr - based amorphous alloy, Pd - based amorphous alloy, Pt - based amorphous alloy or La - based amorphous alloy; the material of the anti - adhesion film is Ir - based amorphous alloy.
[0050] Optionally, the raw materials of the Ir - based amorphous alloy include components of Ir a Ta b Ni c X dAn amorphous alloy material, wherein X includes one or more of Ru, Os, Rh, Pd, Pt, and Nb, and a, b, c, and d represent atomic composition percentages, where the range of a is 18 to 45, the range of b is 20 to 46, the range of c is 18 to 32, and the range of d is 1.5 to 38.
[0051] The raw materials of the Zr-based amorphous alloy include a composition of Zr e Cu f Al g Y h An amorphous alloy material, wherein Y includes one or more of Ni, Nb, Be, and Hf, and e, f, g, and h represent atomic composition percentages, where 38 ≤ e ≤ 65, 0 ≤ f ≤ 45, 0 ≤ g ≤ 15, and 0.1 ≤ h ≤ 20. Or the raw materials of the Zr-based amorphous alloy include a composition of Zr e Cu f Be i Ti j Ni k An amorphous alloy material, where e, f, i, j, and k represent atomic composition percentages, where 30 ≤ e ≤ 50, 6 ≤ f ≤ 15, 20 ≤ i ≤ 28, 10 ≤ j ≤ 30, and 0 ≤ k ≤ 15; for example: Zr 35 Ti 30 Be 26.75 Cu 8.25 Or Zr 41.2 Ti 13.8 Cu 12.5 Ni 10 Be 22.5 。
[0052] The raw materials of the Pd-based amorphous alloy include a composition of Pd m Ni n Cu o Ni p An amorphous alloy material, where m, n, o, and p represent atomic composition percentages, where 40 ≤ m ≤ 50, 5 ≤ n ≤ 15, 20 ≤ o ≤ 35, and 10 ≤ p ≤ 20.
[0053] The raw materials of the Pt-based amorphous alloy include a composition of Pt q Cu r Ni s P t An amorphous alloy material, where q, r, s, and t represent atomic composition percentages, where 40 ≤ q ≤ 65, 10 ≤ r ≤ 20, 2 ≤ s ≤ 8, and 15 ≤ t ≤ 25, for example: Pt 57.5 Ni 5.3 Cu 14.7 P 22.5 。
[0054] The raw materials of the La-based amorphous alloy include an amorphous alloy material with the composition of La u Al v Ni w Cu x Co y , where u, v, w, x, and y represent the atomic composition percentages. Among them, 55 ≤ u ≤ 62, 10 ≤ v ≤ 25, 0 ≤ w ≤ 20, 0 ≤ x ≤ 25, and 0 ≤ y ≤ 5.
[0055] Please refer to Figures 2 to 4 , optionally, in this embodiment, the Zr-based metallic glass is Zr 55 Cu 30 Ni 5 Al 10 (at.%), which has excellent thermoplastic forming properties and a relatively wide single reflection. Its crystallization temperature (Tx) and glass transition temperature (Tg) are 411.8 °C and 491.8 °C respectively, and it can achieve the replication of the micro-nano structure 101 at a relatively low temperature. In other embodiments, metallic glasses such as La-based and Pt-based can also be used to prepare the template 20.
[0056] Optionally, in this embodiment, the material of the anti-adhesion film is Ir 29.8 Ta 34.6 Ni 29.3 Nb 6.3 amorphous alloy, whose Tg and Tx are 830 °C and 948 °C respectively. The anti-adhesion film has an amorphous structure and high hardness (the surface hardness can reach 12.03 GPa), which not only significantly improves the anti-wear and anti-adhesion properties of the mold surface, but also has high-temperature resistance, enabling the metal mold 30 to remain stable during the high-temperature forming process at 620 °C, and the durability can reach more than 30 times without obvious peeling.
[0057] The bonding force between the amorphous anti-adhesion film and the template 20 can reach 423.4 mN, which is better than other DLC coatings in the industry.
[0058] Optionally, since the main elements on the surface of D-K9 glass, namely O, Si, B, Ba, Na, and K, are also in an amorphous distribution. During the vacuum hot pressing forming process at 620 °C, the anti-adhesion film has an isolation effect on the glass surface, which can prevent the elements on the glass surface from diffusing into the anti-adhesion film, thereby making the metal mold 30 have anti-adhesion properties.
[0059] In some embodiments, in the coating step, an Ir-based amorphous alloy is used as the target, and the template 20 is coated by pulsed laser deposition technology to deposit the anti-adhesion film on the template 20.
[0060] Optionally, the target is rectangular, with a length of 12 mm and a width of 9 mm. The pulsed laser deposition technique can precisely transfer the target composition by evaporating the target with high-energy laser pulses, ensuring the chemical uniformity and amorphous structure of the anti-adhesion film, thereby guaranteeing a low surface roughness (only 4.6 nm) and excellent bonding performance (bonding force up to 423.4 mN) on the mold surface. Compared with traditional coating methods (such as sputtering or chemical vapor deposition), the pulsed laser deposition technique can rapidly deposit amorphous alloy films at a lower substrate temperature, avoid the risk of crystallization, and simultaneously form atomic-level metallurgical bonding, enhancing the adhesion between the anti-adhesion film and the template 20.
[0061] Please refer to Figures 2 to 4 , in some embodiments, the pulsed laser deposition technique is implemented using a pulsed laser emitter 50, the frequency of the pulsed laser emitter 50 is 2 Hz, and the single-pulse energy of the pulsed laser emitter 50 is 50 mJ.
[0062] Optionally, the low frequency of 2 Hz combined with the moderate pulse energy of 50 mJ not only ensures the effective evaporation of the target but also avoids defects (such as particle accumulation or stress concentration) in the anti-adhesion film caused by an excessive deposition rate, thereby forming a uniform and dense anti-adhesion film with a controllable thickness (such as up to 85 nm) and a surface roughness as low as 4.6 nm, ensuring that the metal mold 30 has excellent anti-adhesion and optical replication accuracy.
[0063] Please refer to Figures 2 to 4 , in some embodiments, the template 20 has a first coefficient of thermal expansion, the anti-adhesion film has a second coefficient of thermal expansion, and the ranges of the first coefficient of thermal expansion and the second coefficient of thermal expansion are greater than zero and less than 10 ppm / K.
[0064] Optionally, in this embodiment, the first coefficient of thermal expansion of the Zr-based metallic glass is 9.51 ppm / K, and the second coefficient of thermal expansion of the anti-adhesion film is 7.08 ppm / K. The first coefficient of thermal expansion and the second coefficient of thermal expansion are close and both are low, so that the thermal expansion consistency can be maintained during the high-temperature hot embossing process, avoiding the peeling of the anti-adhesion film or the deformation of the metal mold 30 caused by thermal stress. The structural stability of the metal mold 30 in the repeated high-temperature and high-pressure environment is improved, ensuring that the micro-nano structure 101 accuracy remains consistent after multiple uses, thereby extending the service life of the metal mold 30 (at least 30 cycles without peeling), and enhancing the optical performance consistency of the glass MLAs, providing a reliable process basis for large-scale production.
[0065] Please refer to Figures 2 to 4 , in some embodiments, an atomic bond connection is formed between the template 20 and the anti-adhesion film.
[0066] Optionally, the anti-adhesion film forms an atomic-level metallurgical bond with the template 20, with a bonding force as high as 423.4 mN, far exceeding that of DLC coatings (161.5 mN) and polycrystalline coatings (34.8 mN). This atomic bonding not only improves the adhesion of the anti-adhesion film, making it less likely to peel off during high-temperature and high-pressure processes, but also enhances the overall durability and oxidation resistance of the metal mold 30 through the uniform distribution of interface elements (without segregation).
[0067] Please refer to Figures 2 to 4 , in some embodiments, the replication step includes the following steps:
[0068] S31: Polish the template 20. The template 20 can be polished with sandpaper to make the surface roughness of the template 20 as low as 2.23 nm, providing a high-quality basis for the subsequent replication of the micro-nano structure 101;
[0069] S32: Stack the template 20 and the master mold 10 and place them together in a heating chamber. Evacuate the heating chamber to a vacuum degree lower than 0.001 Pa;
[0070] S33: Apply a first predetermined pressure on the template 20 to press the master mold 10 and the template 20 tightly;
[0071] S34: Heat the template 20 to a first predetermined temperature, and increase the first predetermined pressure to a second predetermined pressure, where the second predetermined pressure is greater than the first predetermined pressure, so that the template 20 replicates the micro-nano structure 101;
[0072] S35: Then heat the template to a second predetermined temperature, where the second predetermined temperature is greater than the first predetermined temperature, and perform crystallization treatment on the template 20 replicated with the micro-nano structure 101.
[0073] Optionally, the magnitude of the first predetermined pressure can be 0.2 kN, the first predetermined temperature can be 470 °C, heat the template 20 to 470 °C at a rate of 50 °C / min, and then heat the template 20 to the second predetermined temperature at a rate of 50 °C / min. The second predetermined temperature can be 550 °C.
[0074] Optionally, place the template 20 on the master mold 10, heat the template 20 in a vacuum environment and apply a downward pressure of 0.2 kN to make the template 20 pre-contact with the master mold 10. After the temperature rises to 470 °C, the first predetermined pressure rises to the second predetermined pressure, and the second predetermined pressure rises to 0.4 kN. The micro-nano structure 101 of the master mold 10 is accurately replicated by using the thermoplasticity of the metallic glass, avoiding air interference and oxidation. Then raise the temperature of the template 20 to 550 °C for crystallization treatment. The crystallization treatment can convert the template 20 into a stable crystalline state, enhancing its high-temperature stability (Tm reaches 840 °C). The mechanical strength and durability of the metal mold 30 are also improved through the crystallization treatment.
[0075] Please refer to Figures 2 to 4 , in some embodiments, the step S34 includes:
[0076] S331: At the second predetermined temperature, maintain the second predetermined pressure, and keep the template 20 and the master mold 10 at a constant temperature for a predetermined time. The predetermined time can be 5 minutes, and at the same time, the second predetermined pressure is maintained at 0.4 kN to allow the template 20 to fully crystallize and the micro-nano structure 101 to fully form;
[0077] S332: Cool the template 20 to the third predetermined temperature and unload the second predetermined pressure. The third predetermined temperature is lower than the first predetermined temperature, and the third predetermined temperature can be 450 °C;
[0078] S333: Cool the template 20 to room temperature.
[0079] Please refer to Figures 2 to 4 , in some embodiments, the first predetermined temperature is 470 degrees Celsius, and the second predetermined temperature is 550 degrees Celsius.
[0080] Optionally, 470 °C is higher than the Tg (411.8 °C) of the template 20, and the template 20 is in the supercooled liquid region (SLR). At this time, the template 20 has the best thermoplasticity and can efficiently replicate the micro-nano structure 101 on the master mold 10; 550 °C exceeds the Tx (491.8 °C) of the template 20, ensuring that the template 20 is fully crystallized and transformed into a stable amorphous alloy state, enhancing the high-temperature stability and hardness.
[0081] Please refer to Figure 5 , where the solid line is the temperature curve and pressure curve of the metal mold, and the dashed line is the temperature curve and pressure curve of the optical glass. Figure 5 In
[0082] Optionally, immerse the template 20 and the master mold 10 in a 1 mol / L sodium hydroxide (NaOH) solution. The sodium hydroxide solution can chemically corrode the connection between the metal mold and the master mold, which can facilitate demolding, and then use an ultrasonic cleaner for vibratory demolding.
[0083] The present invention also provides a metal mold 30, which is prepared by the above-mentioned method for preparing a high-temperature resistant mold with a micro-nano structure 101 array. The specific structure of the metal mold 30 refers to the above-mentioned embodiments. Since all the technical solutions of the above-mentioned all embodiments are adopted, it also has all the beneficial effects brought by the technical solutions of the above-mentioned embodiments, which will not be elaborated here one by one.
[0084] Please refer to Figure 4 , in some embodiments, the metal mold 30 is used for hot pressing an optical glass 40, and the material of the optical glass 40 is D-K9. The embodiments of the present application also provide a hot pressing method, including the following steps:
[0085] T1: Apply a pressure of 0.2 kN between the optical glass 40 and the metal mold 30 at room temperature;
[0086] T2: Continuously heat at a heating rate of 50 °C / min to bring the metal mold 30 and the optical glass 40 to 620 °C and hold for 1 minute;
[0087] T3: Cool the optical glass 40 to 400 °C and keep a pressure of 0.2 kN between the optical glass 40 and the metal mold 30;
[0088] T4: Unload the pressure, cool the optical glass 40 to room temperature, and put the optical glass 40 and the metal mold 30 together into a container filled with alcohol, and use an ultrasonic cleaner for vibratory demolding.
[0089] Optionally, in the structural design of the metal mold 30, the shape, size, and arrangement of the micro-nano structure 101 array can be adjusted according to the requirements of specific optical elements to achieve diversified micro-nano structure 101 designs and meet the needs of different functions. In terms of the molding process, in addition to hot embossing and injection molding, the metal mold 30 can also be applied to other thermoplastic molding processes, such as extrusion molding, blow molding, etc., and can also be applied to the hot pressing of metals, expanding the application scope and market space of the metal mold.
[0090] The above are only optional embodiments of the present application and are not used to limit the present application. For those skilled in the art, various changes and modifications can be made to the present application. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included within the scope of the claims of the present application.
Claims
1. A method for preparing a high temperature resistant mold having a micro-nano structure array, characterized in that: The steps include: Molding, preparing a master mold, wherein the master mold is processed with a micro-nano structure; Cutting, preparing raw materials, the material of the raw materials is metallic glass, and cutting a template of a predetermined shape on the raw materials; Replicating, heating to soften the template, and allowing the template to replicate the micro-nano structure; Coating: coating an anti-adhesive film on the template, the material of the anti-adhesive film is metallic glass, and the anti-adhesive film covers the micro-nano structure to process the template into a metal mold.
2. The method for preparing a high temperature resistant mold having a micro-nano structure array according to claim 1, characterized in that: The material of the template is Zr-based amorphous alloy, Pd-based amorphous alloy, Pt-based amorphous alloy or La-based amorphous alloy; the material of the anti-adhesive film is Ir-based amorphous alloy.
3. The method for preparing a high temperature resistant mold having a micro-nano structure array according to claim 2, characterized in that: In the coating step, the Ir-based amorphous alloy is used as a target material, and a pulsed laser deposition technology is used to coat the template, so as to deposit the anti-adhesive film on the template.
4. The method for preparing a high temperature resistant mold having a micro-nano structure array according to claim 3, characterized in that: The pulse laser deposition technique is implemented using a pulse laser emitter, the frequency of the pulse laser emitter is 2 Hz, and the single pulse energy of the pulse laser emitter is 50 mJ.
5. The method for preparing a high temperature resistant mold having a micro-nano structure array according to claim 1, characterized in that: The template has a first thermal expansion coefficient, the anti-adhesive film has a second thermal expansion coefficient, and the first thermal expansion coefficient and the second thermal expansion coefficient are both in a range of greater than zero and less than 10 ppm / K.
6. The method for preparing a high temperature resistant mold having a micro-nano structure array according to claim 1, characterized in that: The template is circular, and the diameter of the template ranges from 2 to 15 mm, and the thickness of the template ranges from 1 to 5 mm.
7. The method for preparing a high temperature resistant mold having a micro-nano structure array according to any one of claims 1 to 6, characterized in that: The copying step comprises the following steps: S31: polishing the template; S32: stacking the template and the master mold and placing them together in a heating chamber, and evacuating the heating chamber; S33: applying a first predetermined pressure on the template to press the master mold and the template tightly; S34; Heating the template to a first predetermined temperature, increasing the first predetermined pressure to a second predetermined pressure, wherein the second predetermined pressure is greater than the first predetermined pressure, so that the template replicates the micro-nano structure; S35: heating the template to a second predetermined temperature, wherein the second predetermined temperature is greater than the first predetermined temperature, so as to perform a crystallization process on the template on which the micro-nano structure is replicated.
8. The method for preparing a high temperature resistant mold having a micro-nano structure array according to claim 7, characterized in that: The step S34 includes: S331: maintaining the second predetermined pressure at the second predetermined temperature, and keeping the template and the master mold warm for a predetermined time; S332: Cooling the template to a third predetermined temperature and unloading the second predetermined pressure, wherein the third predetermined temperature is lower than the first predetermined temperature; S333: Cooling the template to room temperature.
9. The method for preparing a high temperature resistant mold having a micro-nano structure array according to claim 8, characterized in that: The first predetermined temperature is 470 degrees Celsius, the second predetermined temperature is 550 degrees Celsius, and the third predetermined temperature is 450 degrees Celsius.
10. A metal mold, characterized in that: The mold is prepared by the method for preparing a high temperature resistant mold having a micro-nano structure array according to any one of claims 1 to 9.
Citation Information
Patent Citations
Plastic hot stamping micro-molding mold taking metal glass as base body and preparation method
CN102615820A
Mould and mould film-coating method
CN104129017A
Preparation method of metal film mold with surface micro-nano structure and metal film mold midbody
CN109722666A
Micro-nano element for realizing dynamic light field regulation and preparation method thereof
CN116750710A
Optical glass mother board manufacturing process
CN117142776A